1965
DOI: 10.1128/aem.13.6.851-857.1965
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Inactivation Characteristics of Bacillus subtilis Spores at Ultrahigh Temperatures1

Abstract: The thermal inactivation characteristics of Bacillus subtilis A spores suspended in skim milk with the use of large-scale ultrahigh temperature (UHT) processing equipment were investigated in terms of survival as measured with two plating media. Data on survival immediately after UHT treatments were recorded in temperature-survivor curves, time-survivor curves, and decimal reduction time (DRT) curves. The temperature-survivor curves emphasized that inactivation is accelerated more by increases in the treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

1967
1967
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 10 publications
2
25
0
Order By: Relevance
“…The spore suspension of B. subtilis A was prepared according to the method of Edwards et al (1965a) on Fortified Nutrient Agar (FNA) containing (g 1-') : beef extract, 3.0; peptone, 5.0; glucose, 1.0; NaCI, 8.0; agar, 20.0; MnCI, solution (5 g I-'), 1 ml; 50 ml of a modified mineral solution containing (g I-'): ZnSO, . Spore preparation was carried out as for strain 5230 except that incubation was at 45°C and the differential centrifugation started at 650 g, up to 4150 g, in increments of After a portion was retained as non-freeze dried control, each spore suspension was divided equally between three screw-capped test tubes (16 x 150 mm) containing sterile 3 mm glass beads, and freeze dried at -50°C to -55°C for 24 h under a vacuum of 25 mm Hg. After lyophilization, the contents of each test tube were suspended in Butterfield's buffer (pH 7.2) (Leininger 1976), mineral oil (light petrolatum), olive oil or vegetable oil.…”
Section: Store Suspension Preparationmentioning
confidence: 99%
“…The spore suspension of B. subtilis A was prepared according to the method of Edwards et al (1965a) on Fortified Nutrient Agar (FNA) containing (g 1-') : beef extract, 3.0; peptone, 5.0; glucose, 1.0; NaCI, 8.0; agar, 20.0; MnCI, solution (5 g I-'), 1 ml; 50 ml of a modified mineral solution containing (g I-'): ZnSO, . Spore preparation was carried out as for strain 5230 except that incubation was at 45°C and the differential centrifugation started at 650 g, up to 4150 g, in increments of After a portion was retained as non-freeze dried control, each spore suspension was divided equally between three screw-capped test tubes (16 x 150 mm) containing sterile 3 mm glass beads, and freeze dried at -50°C to -55°C for 24 h under a vacuum of 25 mm Hg. After lyophilization, the contents of each test tube were suspended in Butterfield's buffer (pH 7.2) (Leininger 1976), mineral oil (light petrolatum), olive oil or vegetable oil.…”
Section: Store Suspension Preparationmentioning
confidence: 99%
“…Some spore crops were inhibited in CaDPA medium but were all activated similarly when the CaDPA was incorporated in the h a 1 dilution prior to plating. A medium of this type used to study thermal inactivation characteristics of B. subtilis spores a t ultrahigh temperatures (Edwards, Busta & Speck, 1965a) resulted in larger D values than on a medium without CaDPA. Additionally the concave-upwards time-survival curves obtained with standard plating medium were not observed with CaDPA supplemented medium, the higher counts in the supplemented medium falling essentially on a straight line on a log% survivorstime graph.…”
Section: (Iii) Use Of Other Additivesmentioning
confidence: 99%
“…It is quite possible that in evaporated milk the spores of our strain B. subtilis Bac 1-12 could gradually develop increasing heat resistance during the heating, as a slowly evoked protective response within the spores (see Alderton, Thompson & Snell, 1964). These observations are not in agreement with those of Franklin et al (1958) who obtained lower numbers of survivors in milk than in water as well as some acceleration of the spore inactivation in milk by increasing the heating temperature, The phenomenon described by Alderton et al (1964) was later observed by Edwards et al (1965a) and in their experiments it resulted in concave time survivor curves of the spores of B. subtilis strain A with a z value of 16 in the lower temperature range (113"-120") and 33 in the higher temperature range (121"-135"). The same authors observed an increase in surviving spores of B. subtilis strain A, but only in the lower temperature range, when the recovery medium was enriched with Ca2+ and sodium dipicolinate, as mentioned by Doi (1961) and studied in practice by Busta & Ordal (1964).…”
Section: Discussionmentioning
confidence: 56%
“…This strain, Bac 1-11, seemed to have a much higher thermal resistance than has been described for this genus, for example Liociardello & Nickerson (1963) gave a D112.5 value of 0.07 rnin for the strain var. niger; Edwards, Busta & Speck (1965a), observed a Du2.5 value of 0.1-0.3 min for strain A; Lechowich & Ordal (1962), obtained a D,,., value of 10 min for strain L ; Ridgway (1958), gave a D,, value of c. 12.5 rnin for strain C, while Donnellan, Nags & Levinson (1964) recorded a D,, value of 13 rnin for strain ATCC 6051. The thermal resistance also exceeded that of various other strains ofB.…”
mentioning
confidence: 93%